2021
DOI: 10.1007/s10592-020-01324-z
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of regionally extinct peregrine falcons (Falco peregrinus) and unassisted recovery without genetic bottleneck in southern England

Abstract: The peregrine falcon (Falco peregrinus) has been affected by persecution, pollution, trade and habitat degradation, but it is considered a flagship conservation success story because of successful reintroductions. However, in the UK there were never formal reintroduction programmes for peregrine falcons, and it appears that UK populationsand specifically the Sussex peregrines of the English south coastrecently recovered from a population crash unassisted. To study this, we obtained samples from contemporary po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Additionally, unlike another non-augmented populations studied in England (Weaving et al 2021), we observed increases in levels and distribution of genetic diversity following the decline and recovery. Our results, coupled with recent results from Weaving et al (2021), provide valuable inference for assessing results of unassisted recovery of Peregrine populations but also highlight the importance of evaluating the impacts of declines on a case-by-case basis. It is the interplay of ecological, demographic and microevolutionary processes that shapes the trajectory of genetic diversity through time.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Additionally, unlike another non-augmented populations studied in England (Weaving et al 2021), we observed increases in levels and distribution of genetic diversity following the decline and recovery. Our results, coupled with recent results from Weaving et al (2021), provide valuable inference for assessing results of unassisted recovery of Peregrine populations but also highlight the importance of evaluating the impacts of declines on a case-by-case basis. It is the interplay of ecological, demographic and microevolutionary processes that shapes the trajectory of genetic diversity through time.…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, unlike another non‐augmented populations studied in England (Weaving et al . 2021), we observed increases in levels and distribution of genetic diversity following the decline and recovery. Our results, coupled with recent results from Weaving et al .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The British peregrine population later declined sharply due to widespread organochlorine pesticide use (Ratcliffe, 1970). Cyclodienes applied as insecticides to seeds caused mortality in seed-eating birds and bioaccumulation and eggshell thinning in their predators (Weaving et al, 2021). By the 1960s, the UK peregrine population had fallen by 80% compared to its pre-war abundance (RSPB, 2021).…”
Section: Technonatural History As Methods and Theorymentioning
confidence: 99%
“…In addition, multiple subspecies possess both island and mainland populations ( F. p. pealei , F. p. cassini , F. p. peregrinator , F. p. ernesti ) or varying levels of migratory behavior depending on local environmental conditions and resource availability ( F. p. anatum , F. p. peregrinus , F. p. babylonicus ; see Table S1; Gu et al, 2021; White, Cade, & Enderson, 2013). Although much genetic research has examined levels of diversity using a restricted set of presumably neutral or functional loci among peregrine falcon populations and subspecies (Bell et al, 2014; Brown et al, 2007; Gangoso et al, 2012; Jacobsen et al, 2008; Johnson et al, 2010; Ponnikas et al, 2017; Sonsthagen et al, 2022; Talbot et al, 2011, 2017; Weaving et al, 2021; White, Sonsthagen, et al, 2013), it remains unclear to what degree genomic diversity varies within the species on a broad geographic scale and whether the observed patterns are expected due to life history differences or spatial constraints that may have developed since subspecies and population differentiation.…”
Section: Introductionmentioning
confidence: 99%